Study of the Load-Bearing Characteristics of Bolts under Asymmetric Freezing Conditions - Jie Dong; Xin Yan; Zhao-Qi Li; Yang Liu; Ying-Hao Zheng; Kai Feng (Applied Sciences, 2023)
To investigate the load-bearing characteristics of anchor rods under asymmetric freezing conditions such as those in cold regions and the effect of frost swelling, a model test device was developed using a controlled-temperature environmental box and a hydraulic actuator. Laboratorial pull-out model tests of anchor rods in soil layers were conducted at different moisture contents and freezing temperatures, the changes in anchor rod pull-out force before and after freezing were quantitatively described, load–displacement relationship curves were prepared, and the frost swelling displacement of anchor rods under asymmetric freezing conditions and the stress evolution of surrounding soil were observed and recorded. The shear strength of the anchor–soil interface increased with decreasing temperature, and the ultimate values of the pull-out force at 0, −3 and −7 °C were 4, 17.04 and 18.1 times greater than those at room temperature, respectively, for 10% water content. The pull-out force of the frozen anchor increased with increasing water content. The bolts were displaced by the freezing expansion force. Their lateral displacements at 0, −3 and −7 °C were 2.9, 3.2 and 3.5 mm, respectively, and their vertical displacements were 0.2, 3.5 and 4.3 mm, respectively, for 10% water content. The total displacement increased with increasing moisture content, and the maximum transverse displacements were 3.5, 3.65 and 3.8 mm for 10, 12 and 14% water contents, respectively, and 4.3, 5.1 and 5.5 mm in the vertical direction, respectively. The ultimate pull-out forces after freezing and thawing were 71, 68 and 52% of that before freezing for 10, 12 and 14% water, respectively.